Evaluating the Impact of Medan City Regional Regulation Number 2 of 2022 on Library Services and Community Literacy Development - Batubara, Syahril; Kusmanto, Heri; Ridho, Hatta; Suriadi, Agus; Thamrin, Husni (East Asian Journal of Multidisciplinary Research, 2024)
This research examines the implementation of Medan City Regional Regulation No. 2 Year 2022 on the Implementation of Libraries and its effectiveness in realizing the objectives of library services in Medan City. Utilizing qualitative research methods, the study analyzes data from interviews, observations, and documentation to assess policy implementation based on Van Mater Van Hord's theory, focusing on policy size and objectives, resources, communication, and environmental factors. Findings indicate that the regulation has positively impacted library services, encouraging reading habits and knowledge dissemination through various programs and innovations, such as mobile libraries and digital initiatives. The Medan City Library and Archives Office, supported by 67 staff members and adequate financial resources, has effectively utilized inter-organizational communication to coordinate efforts. Despite challenges like limited staff, the economic, social, and political environments remain supportive, with no significant obstacles. The implementation also includes digitalization efforts like the e-pada application, aimed at increasing public access to information and mitigating the adverse effects of social media.